FORMING PRO-SOCIAL BEHAVIOR OF ADOLESCENTS: THE ESSENCE AND MECHANISMS OF ORGANIZATION OF EDUCATIONAL PROCESS SUBJECTS' INTERACTION (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The author reveals the peculiarities of formation of pro-social behavior of adolescents that draw attention of scientists-practitioners and society, bearing in mind the difficult socio-economic, political and military situation in Ukraine. In the article, the authentic determination of 'pro- social behavior' is presented as a complex and social psychological phenomenon that develops in the process of a personality formation. The essence and mechanisms of organization of educational process subjects' interaction are revealed; results of experimental activity (criteria and indices of pro-social behavior of vulnerable adolescents are determined: the problematic areas of activity are defined: teenagers' inability of proper conduct in conflict situations, of negative answers to a risky offer, insufficient motivation to pro-social actions, limited pro-social behavior manifestations in everyday life; the rating of game technology application in the educational process of educational institutions, and successful practical introductions of game technologies of teenagers'prosocial behavior formation due its essential features: personal orientation, dialogical orientation, two-centered relations between participants, are given.
Keywords: pro-social behavior, adolescence, vulnerable categories of teenagers, game technology, constructive interaction, social educator